Improving persuasive speaking skills using the rouse-relate-respond (3Rs) template in an online learning environment - Mabini, Daniel Adan; Zara, Nerissa O.; Baetiong, Lourdes R.; Caluag, Diana G. (Quezon City College of Education, University of the Philippines Diliman, 2021)
Public speaking remains to be a challenging task for non-native English public speakers due to communication apprehension (Bastida & Yapo, 2019) and problems in organizing in organizing and outlining ideas (Lee & Liang, 2012). Despite this, there is a dearth of local literature that addresses this concern (Del Villar, 2010), especially in public secondary schools. This study sought to determine how the use of an alternative rhetorical pedagogy-the 3Rs (Rouse-Relate-Respond) guided oral presentation (GOP) in an online learning environment - would improve persuasive speaking skills, specially structure and organization, content development, delivery, and confidence. The participants of the study were 18 grade 10 students from a public secondary school in Southern Tagalog province in the Philippines. Data were obtained through the Public Speaking Competence Rubric (Schreiber et al., 2012 in Mortaji, 2018), Personal Report of Public Speaking Anxiety (McCroskey, 1970), and Surveys on Students' Perception about Online Learning (Platt, Raile, & Yu, 2014). Wilcoxon Signed Rank test was used to compute if there was a significant difference in the persuasive speaking skills of the participants before and after the training, while Pearson Product Moment Correlation was used to test the correlation between the online learning environment and the participants' persuasive speaking skills. Conceptual content analysis of the stimulated recall interview, pre-and posttest manuscripts, and PRPSA answers were used to gather qualitative data. The results showed that the participants' persuasive speaking skills improved after the training, but there was no significant correlation between the online learning environment where the investigation was conducted and the participants' improved persuasive speaking skills. The participants were able to demonstrate a careful choice of words, formulate an introduction that orients audience to the speaker and topic, show effective use of vocal expression and paralanguage, successfully adapt the presentation to the audience, and have lessened communication apprehension. Moreover, data revealed that use of the 3Rs template, direct instruction of skills, time for research and practice, and teacher's guidance helped improve the participants' persuasive speaking skills. The use of the 3Rs GOP template and the characteristics of the training that helped improve persuasive speaking skills were recommended as an alternative rhetorical pedagogy.
Thesis
Keywords: Public speaking -- Study and teaching (Secondary) -- Philippines -- Southern Tagalog; Communication -- Study and teaching (Secondary) -- Philippines -- Southern Tagalog; English language -- Study and teaching (Secondary) -- Foreign speakers; English language -- Rhetoric -- Study and teaching (Secondary)